Charge and spin effects in mesoscopic Josephson junctions: Сверхпроводимость и мезоскопические структуры - Krive, Ilya V.; Kulinich, Sergei I.; Shekhter, Robert I.; Jonson, Mats (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We consider the charge and spin effects in low dimensional superconducting weak links. The firstpart of the review deals with the effects of electron—electron interaction in Superconductor/Luttinger liquid/Superconductor junctions. The experimental realization of this mesoscopic hybridsystem can be the individual single wall carbon nanotube that bridges the gap between two bulksuperconductors. The dc Josephson current through a Luttinger liquid is evaluated in the limits of perfectlyand poorly transmitting junctions. The relationship between the Josephson effect in a long SNSjunction and the Casimir effect is discussed. In the second part of the paper we review the recent resultsconcerning the influence of the Zeeman and Rashba interactions on the thermodynamical properties of ballistic S–QW–S junction fabricated in two dimensional electron gas. It is shown that in magnetically controlled junction there are conditions for resonant Cooper pair transition which results in giant supercurrent through a tunnel junction and a giant magnetic response of a multichannel SNSjunction. The supercurrent induced by the joint action of the Zeeman and Rashba interactions in 1D quantum wires connected to bulk superconductors is predicted.